A Study of Rajasthan State R.T.C - Planning Commission, Government of India (Planning Commission, Government of India, 1968)
The interim report on the Rajasthan State Road Transport Corporation (RSRTC) evaluates operational inefficiencies, financial challenges, and management issues, providing strategic recommendations to enhance profitability and service delivery. Established in 1964, RSRTC faced low vehicle utilization, inadequate maintenance, and escalating financial losses by 1967. Key recommendations include restructuring management roles, improving maintenance through central workshops, implementing cost-control measures, optimizing routes, adjusting tariffs, and decentralizing authority to regional managers. The report emphasizes performance appraisal systems, prudent investment evaluation, and budgetary controls to ensure long-term financial sustainability and operational effectiveness of RSRTC.
Committee on Plan Projects Planning Commission Government of India January 1968
Committee on Plan Projects Planning Commission Government of India January
Keywords: Rajasthan State Road Transport Corporation; RSRTC; Fleet Management; Operational Efficiency; Vehicle Utilization; Financial Assessment; Cost Management; Revenue Generation; Maintenance Strategies; Management Restructuring; Performance Appraisal; Decentralization